2001
DOI: 10.1111/j.1547-5069.2001.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Experiences of Restructuring in Three Ontario Hospitals

Abstract: Restructuring intensifies structural weaknesses in professions, such as nursing, whose members are primarily employed by bureaucracies. Nurses may not find survivor syndrome a useful model to explain their low morale following restructuring because it identifies nurses as "patients" in need of therapy. An empowerment model that takes into account nurses' concerns about uncertainty and integration may be more fruitful for devising strategies to enhance their ability to practice effectively in hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 9 publications
6
74
0
6
Order By: Relevance
“…Nurses who survived the layoffs were expected to be more productive and care for an increased number of acutely ill patients (RNAO, 2003). Nurses felt overworked, stressed and betrayed by their organizations (Baumann et al, 2001). Their job satisfaction decreased as they provided complex care to a large number of patients (O'Brien-Pallas et al, 2004).…”
Section: Background On Health Sector Reform and Its Effect On Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses who survived the layoffs were expected to be more productive and care for an increased number of acutely ill patients (RNAO, 2003). Nurses felt overworked, stressed and betrayed by their organizations (Baumann et al, 2001). Their job satisfaction decreased as they provided complex care to a large number of patients (O'Brien-Pallas et al, 2004).…”
Section: Background On Health Sector Reform and Its Effect On Nursesmentioning
confidence: 99%
“…Work intensification is seen across occupations and sectors, though women, people older than 40 and service-sector and public sector workers perceive more of an increase in work effort (Green, 2004). In Canada, concerns are being raised about how nurses' fast pace, time pressures and intense work affect their commitment, job satisfaction and the overall quality of their work life (Baumann et al 2001;Blythe, Baumann and Giovannetti, 2001). A European study (Hasselhorn et al, 2005) and a study in progress in Canada (O'Brien-Pallas et al, 2004) are showing an inverse relationship between work intensification and job satisfaction for nurses.…”
Section: The Theory and The Conceptual Model Of Factors Associated Wimentioning
confidence: 99%
“…Une étude récente au Canada auprès du personnel infirmier révèle une confusion de rôle au sein de la profession infirmière et entre le personnel infirmier et les autres professionnels de la santé (Besner et al, 2005). Cette confusion de rôle pourrait s'expliquer par les changements fréquents dans la division du travail du personnel hospitalier à la suite des réformes du système de santé (Blythe, Baumann et Giovannetti, 2001;Decter, 1997;Workman, 1996).…”
Section: Problématiqueunclassified
“…Toutefois, peu d'études en science infirmière utilisent spécifiquement ce concept ou la théorie des rôles. (Barter, McLaughlin et Thomas, 1997;Blythe et al, 2001;Jervis, 2002;Rhéaume et al, 2007;Warr, 2002). D'après ces écrits, la distinction entre les rôles des infirmières et des infirmières auxiliaires n'est pas toujours claire.…”
Section: Problématiqueunclassified
“…The nursing profession seems to be in difficulty (Baumann & Blythe, 2003;Baumgart, 1997;Buchan, Hancock & Rafferty, 1997;Reinhardt, 1996) Why are nursing staff now less satisfied? Signs of nursing dissatisfaction appeared in the early to mid-1990s as hospitals undertook restructuring and downsizing initiatives in response to lower levels of financial support from country or regional governments Aiken , Sochaski & Anderson, 1996; Armstrong-Stassen, Cameron & Horsburgh, 1996;Blythe, Baumann & Giovannetti, 2001;Brannon, 1996;Brown, Arnetz & Petersson, 2003;Burke, 2004;Kovner & Gergen, 1998;Laschinger, Sabiston, Finegan & Shamian, 2001 ;Mesch, McGrew, Pescosolido & Haugh, 1999;Robertson & Dowd, 1996;Shanahan, Brownell & Roos, 2001;Shortell, O'Brien & Carman, 1995;Woodward, Shannon, Cunningham, McIntosh, Lendrum, Rosenblum & Brown, 1999). These researchers reported that these restructuring and downsizing efforts were associated with increased levels of job dissatisfaction, higher levels of exhaustion and cynicism (burnout), high levels of psychological distress, a negative impact on hospital functioning, lower levels of hospital upkeep, and greater intentions to leave the profession Now, almost two decades later, the health care sector is again the target of restructuring, downsizing and cost cutting as governments again attempt to deal with budget shortfalls.…”
mentioning
confidence: 99%